Sickness presenteeism explained by balancing perceived positive and negative effects - Lohaus, Daniela; Habermann, Wolfgang; Nachreiner, Malte (Frontiers in Psychology, 2022)
Within the ever-growing body of research on sickness presenteeism, studies of perceived consequences are scarce and equally rare are joint considerations of beneficial and harmful effects. This study examined how experienced and expected consequences of the behavior are related to presenteeism. Positive and negative effects were considered simultaneously and comprehensively. This approach allowed us to capture the trade-off process of individuals in deciding to work or call in sick when ill. In a cross-sectional online survey, 591 working adults in Germany rated a thoroughly developed pool of specific experienced or potential consequences of working while sick and gave an overall judgment of effects. The results show that perceptions of effects are consistent with behavior. Individuals who exhibit presenteeism do so primarily because of work-related effects such as the completion of one’s work tasks and the meeting of deadlines. Few specific effects stand out and can largely explain attendance behavior and the overall assessment of effects. The findings are consistent with the assumptions of the health belief model and the expectancy value theory of work motivation and they relate to the health-performance framework. They demonstrated that benefits and costs of the behavior are simultaneously weighed in the decision to engage in presenteeism or not.